Pretreatment PET/CT Standardized Uptake Values Play a Role in Predicting Response to Treatment and Survival in Patients with Small Cell Lung Cancer - DANE, FAYSAL (KARGER, 2016)
Background: We investigated the role of standardized uptake values (SUVs) of the primary tumor in small cell lung cancer (SCLC) patients. Patients and Methods: The relationship between SUV and response to treatment was investigated using receiver operating characteristic (ROC) curve analysis, and the efficient cut-off value for detecting response to treatment was determined. The effects of SUV on response to treatment and survival were investigated. Results: 90 patients with a median age of 58 years (range 39-83 years) were included. Median follow-up was 11 months. The suitable cut-off SUV for determination of response was found to be 10 in ROC analysis. The sensitivity and specificity of this value were 85.7% (95% confidence interval (95% CI) 63-96) and 61.8% (95% CI 49-73) (area under the curve 0.783; p = 0.0001), respectively. The overall objective response rate in patients with involvement above the cut-off value was 93.3% compared to 59.1% in those with involvement below the cut-off value (p < 0.0001). In uni- and multivariate analysis, favorable effects of limited-stage disease on response to treatment were established (p < 0.05). The effect of an SUV higher than the cut-off value on progression-free survival was borderline (p = 0.085). Conclusion: These data may contribute to identifying prognostic disease characteristics and response to treatment. (C) 2016 S. Karger GmbH, Freiburg
Keywords: Small cell lung cancer; PET/CT; SUV; MANAGEMENT